Improving measurement-based care implementation in youth mental health through organizational leadership and climate: a mechanistic analysis within a randomized trial - Nathaniel J. Williams; Mark G. Ehrhart; Gregory A. Aarons; Susan Esp; Marisa Sklar; Kristine Carandang; Nallely R. Vega; Lauren Brookman-Frazee; Steven C. Marcus (Implementation Science, 2024)
Abstract Background Theory and correlational research indicate organizational leadership and climate are important for successful implementation of evidence-based practices (EBPs) in healthcare settings; however, experimental evidence is lacking. We addressed this gap using data from the WISDOM (Working to Implement and Sustain Digital Outcome Measures) hybrid type III effectiveness-implementation trial. Primary outcomes from WISDOM indicated the Leadership and Organizational Change for Implementation (LOCI) strategy improved fidelity to measurement-based care (MBC) in youth mental health services. In this study, we tested LOCI’s hypothesized mechanisms of change, namely: (1) LOCI will improve implementation and transformational leadership, which in turn will (2) mediate LOCI’s effect on implementation climate, which in turn will (3) mediate LOCI’s effect on MBC fidelity. Methods Twenty-one outpatient mental health clinics serving youth were randomly assigned to LOCI plus MBC training and technical assistance or MBC training and technical assistance only. Clinicians rated their leaders’ implementation leadership, transformational leadership, and clinic implementation climate for MBC at five time points (baseline, 4-, 8-, 12-, and 18-months post-baseline). MBC fidelity was assessed using electronic metadata for youth outpatients who initiated treatment in the 12 months following MBC training. Hypotheses were tested using longitudinal mixed-effects models and multilevel mediation analyses. Results LOCI significantly improved implementation leadership and implementation climate from baseline to follow-up at 4-, 8-, 12-, and 18-month post-baseline (all ps < .01), producing large effects (range of ds = 0.76 to 1.34). LOCI’s effects on transformational leadership were small at 4 months (d = 0.31, p = .019) and nonsignificant thereafter (ps > .05). LOCI’s improvement of clinic implementation climate from baseline to 12 months was mediated by improvement in implementation leadership from baseline to 4 months (proportion mediated [p m ] = 0.82, p = .004). Transformational leadership did not mediate LOCI’s effect on implementation climate (p = 0.136). Improvement in clinic implementation climate from baseline to 12 months mediated LOCI’s effect on MBC fidelity during the same period (p m  = 0.71, p = .045). Conclusions LOCI improved MBC fidelity in youth mental health services by improving clinic implementation climate, which was itself improved by increased implementation leadership. Fidelity to EBPs in healthcare settings can be improved by developing organizational leaders and strong implementation climates. Trial registration ClinicalTrials.gov identifier: NCT04096274. Registered September 18, 2019.